2018
DOI: 10.1111/dom.13212
|View full text |Cite
|
Sign up to set email alerts
|

Running on mixed fuel‐dual agonistic approach of GLP‐1 and GCG receptors leads to beneficial impact on body weight and blood glucose control: A comparative study between mice and non‐human primates

Abstract: AimWe performed acute and chronic studies in healthy and diet‐induced obese animals using mouse‐specific or monkey‐specific dual GLP‐1R/GCGR agonists to investigate their effects on food intake, body weight, blood glucose control and insulin secretion. The selective GLP‐1R agonist liraglutide was used as comparator.MethodsThe mouse‐specific dual agonist and liraglutide were tested in lean wild type, GLP‐1R knockout and diet‐induced obese mice at different doses. A chronic study was performed in DIO mice to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 45 publications
5
29
0
Order By: Relevance
“…An experimentally-increased amount of glycogen in the liver by itself induced hepatic insulin resistance and inhibited new glycogen synthesis in healthy dogs [ 38 ]. Interestingly, novel classes of glucose-lowering drugs, SGLT2 inhibitors and dual GLP1/glucagon agonists, are also known to reduce liver glycogen storage [ 39 41 ]. In addition, clenbuterol could also affect insulin sensitivity through a reduction in inflammation, since these two conditions are closely associated (reviewed in [ 42 , 43 ]).…”
Section: Discussionmentioning
confidence: 99%
“…An experimentally-increased amount of glycogen in the liver by itself induced hepatic insulin resistance and inhibited new glycogen synthesis in healthy dogs [ 38 ]. Interestingly, novel classes of glucose-lowering drugs, SGLT2 inhibitors and dual GLP1/glucagon agonists, are also known to reduce liver glycogen storage [ 39 41 ]. In addition, clenbuterol could also affect insulin sensitivity through a reduction in inflammation, since these two conditions are closely associated (reviewed in [ 42 , 43 ]).…”
Section: Discussionmentioning
confidence: 99%
“…The dual GLP‐1/GCG RA peptide 15 was used as comparator. [ 21 ] To guide dose selection, single dose s.c. administration PK studies in monkeys were performed. Peptide 12 showed a half‐life of 4.7 h, whereas 15 showed a longer half‐life of 7.5 h and a higher exposure.…”
Section: Figurementioning
confidence: 99%
“…SAR425899 was developed for the treatment of patients with T2D and obesity 11 14 aiming to lower glucose at least similar to marketed GLP-1 agonists, but with superior weight loss over GLP-1 receptor mono-agonists. Preclinical studies with SAR425899 clearly demonstrated dual receptor agonism in vitro and in preclinical in vivo studies, with a higher potency for the GLP1R than for the glucagon receptor in order to counterbalance the GCGR mediated increase of blood glucose levels through GLP-1 agonism 11 13 . Because read outs for GCGR specific binding were missing, data from early clinical studies were unable to confirm the dual agonism of SAR425899 in humans 14 .…”
Section: Introductionmentioning
confidence: 99%